SPHEROPLASTS OF THE YEAST CANDIDA UTILIS - Svihla, G. (1961)
Svihla, G. (Argonne National Laboratory, Argonne, Ill.), F. Schlenk, and J. L. Dainko. Spheroplasts of the yeast Candida utilis. J. Bacteriol. 82:808–814. 1961.—The formation and properties of spheroplasts of the yeast Candida utilis, produced by digestion of the cell walls with snail gut juice (Helix pomatia) in isotonic medium, were studied by phase, interference, and ultraviolet microscopy, and tracer techniques. Cells cultivated in the presence of l-methionine, S-methyl-l-methionine, and l-homocysteine (5 μmoles/ml) were more susceptible to enzyme action than ordinary cells. These cells contain increased amounts of S-adenosylmethionine in the vacuole which facilitates ultraviolet microscopy. Spheroplasts are stable in 0.6 m KCl containing 0.04 m phosphate, but are disintegrated by water, sonic vibration, or ultraviolet irradiation. Exposure in isotonic medium to 6 × 10(4) erg/mm(2) energy at 253 mμ breaks the cytoplasmic membrane and liberates the vacuole with membrane intact. The vacuolar membrane may be broken with about three times the initial dose of ultraviolet.